Community Development Policy Toward Poverty Reduction In Indonesia: Case Study Of Coastal Communities In The Southern Coast Of Java Island. - Mukti Fajar (De Montfort University, 2011)
In Indonesia, coastal communities are generally including the poor societies. They have limited access to capital and entrepreneurship capabilities. Some government policies have been carried out as sustainable manner to reduce the poverty for coastal communities. It was implemented by the government in collaboration with the corporation (Bank). The implementation was realized in the form of soft loan program and established the small medium enterprise of fishery. The problems of this research are: (1) how is the implementation of government policy for the development and its influence toward improving the welfare of coastal communities?; (2) What is the policy for managing the small medium enterprise of fisheries to improve the welfare of coastal communities ?; (3) what are the factors that sustained and barrier the implementation of policy to reduction the poverty of coastal communities ?. This is a socio legal research that examines law in society. The law means a form of government policy to empowering of coastal communities, both national regulations and local regulations. The location of the research is conducted in three districts at the southern coast of Java island. The data were collected with documents study, interviews and observation. The conclusion of this research are; First, there are some problems in implementation of policies for the development of coastal communities, namely; (a) There is a gap between formal approach of government policy and the corporation (banks) with the cultural aspects that still embraced by the coastal communities. (b) The community is very dependent on natural conditions (ocean) as the basic of economic activities. Second, The presence of cooperatives is very helpful in improving the welfare of coastal communities in three districts observed. It can be seen by increasing incomes of the community. Third, The supporting factors are communities, governments and other institutions, non-coastal communities, The SMEs fishery and management. Yet, Inhibiting Factors includes cultural factor of the coastal communities, post-production process, natural factors, perception and understanding factors of the society, Bankable approach of MFI Swamitra Mina and the several external factors, for instance economic, technological, socio-cultural policy of the government (law and politics) and industrial environments that become obstructions toward program implementation.